Effect of early ambulation on comfort and vascular complications following electrophysiological studies: A randomized controlled trial - Unnikrishnan Puliyakkuth; Lakshmi Ramamoorthy; Raja J Selvaraj; Hmar Thiak Lalthanthuami; Rani Subramaniyan (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Imposed immobilization after electrophysiological studies (EPS) is known to cause different complications. The current study aims to assess the effect of early ambulation on comfort and vascular complications among patients undergoing transfemoral catheterization for EPS. MATERIALS AND METHODS: Hundred participants were assigned to control and intervention groups (50 each) using block randomization. The control group participants were ambulated at 6 hours after EPS. For the intervention group, participants were kept in the supine position with procedure-side leg extension for the first 2 hours, followed by 30° head-end elevation and turning to the left/right side for 30 min, and finally ambulation at the end of 3 hours. Both groups were assessed for vital signs, groin and back pain, satisfaction, bleeding, hematoma, and bladder pattern at the 6th and 24th hour after EPS. Data analysis was done on an intention-to-treat basis using the Chi-square test, Fisher's exact test, independent student t-test, and Mann-Whitney U test. RESULTS: The level of back pain and groin pain was significantly lower in intervention group after 6 hours (P < 0.001) and after 24 hours (P < 0.05). Urinary problem was not reported in intervention group, whereas Eleven (22%), participants in the control group did not void at 6 hours (P < 0.001). Two patients in intervention group developed bleeding at 6 hours, and one patient in control group developed bleeding at 24 hours. Hematoma development was absent for both groups. CONCLUSION: Early ambulation at 3 hours after EPS is suggested to reduce back pain, groin pain, and urinary problem, without risk for vascular complications.